Biofilm-associated Achromobacter xylosoxidans prosthetic valve infective endocarditis - Lisa-Marie Wackernagel; Judith Kikhney; Tassilo Kruis; Peter Menzel; Matthias Schneider-Reigbert; Herko Grubitzsch; Julia Gogolok; Leif Erik Sander; Florian Kurth; Annette Moter; Tilman Lingscheid (International Journal of Medical Microbiology, 2025)
Background: Infective endocarditis (IE) caused by Gram-negative bacteria is a rare but increasingly recognized emerging infectious disease. Achromobacter xylosoxidans, a Gram-negative non-fermenting opportunistic bacterium, has rarely been associated with IE and its biofilm potential in vivo is unknown. Methods: Specimens from a patient with A. xylosoxidans IE were obtained during cardiac surgery. Fluorescence in situ hybridization was used for visualization of microorganisms within heart valve tissues in combination with 16S rRNA gene PCR and sequencing (FISHseq) for correlation with prior blood culture isolates and to establish a definite diagnosis. The infected prosthetic valve had been implanted six months before. Following implantation, the patient developed relapsing bacteremia with A. xylosoxidans over three months, despite repeated adequate antibiotic treatment. Results: Conventional microbiological analysis of the explanted valve yielded no bacterial growth and prior imaging by repeated positron emission tomography and transesophageal echocardiography did not reveal evidence of infective endocarditis. FISHseq detected A. xylosoxidans in the heart valve samples and demonstrated numerous microorganisms, including FISH-positive, metabolically active bacteria, within in-vivo-grown biofilms. The genomic profile of A. xylosoxidans LB-23–519–25 confirmed the presence of resistance genes commonly found in this intrinsically multidrug-resistant species, which, together with biofilm formation, explains the observed therapeutic failure. Conclusion: Valve culture and imaging failed to identify this case of Gram-negative bacteria IE correctly, but diagnosis of definite IE was eventually established via FISHseq according to the 2023 Duke-ISCVID Criteria. The biofilm-forming potential of A. xylosoxidans and its implications for the efficacy of antimicrobial therapy should be considered in future patients.